Towards Defining Nutrient Conditions Encountered by the Rice Blast Fungus during Host Infection - Wilson, Richard A.; Fernandez, Jessie; Quispe, Cristian F.; Gradnigo, Julien; Seng, Anya; Moriyama, Etsuko; Wright, Janet D. (PLOS ONE, 2012)
Fungal diseases cause enormous crop losses, but defining the nutrient conditions encountered by the pathogen remains elusive. Here, we generated a mutant strain of the devastating rice pathogen Magnaporthe oryzae impaired for de novo methionine biosynthesis. The resulting methionine-requiring strain grew strongly on synthetic minimal media supplemented with methionine, aspartate or complex mixtures of partially digested proteins, but could not establish disease in rice leaves. Live-cell-imaging showed the mutant could produce normal appressoria and enter host cells but failed to develop, indicating the availability or accessibility of aspartate and methionine is limited in the plant. This is the first report to demonstrate the utility of combining biochemical genetics, plate growth tests and live-cell-imaging to indicate what nutrients might not be readily available to the fungal pathogen in rice host cells.